Associations Between Intake of Fermented Dairy Products and Blood Lipid Concentrations Are Affected by Fat Content and Dairy Matrix – The Tromsø Study: Tromsø7 - Machlik, Monika Lund; Hopstock, Laila Arnesdatter; Wilsgaard, Tom; Hansson, Patrik (Frontiers in Nutrition, 2021)
Introduction: Dairy fat is rich in saturated fatty acids known to increase serum low-density lipoprotein cholesterol (LDL-C) concentration, an important risk factor for cardiovascular disease (CVD). However, intake of fermented dairy products has been associated with reduced CVD risk in observational studies. How intakes of different fermented dairy products are associated with blood lipid concentrations may provide a possible explanation for the suggested reduced CVD risk. Aim: To examine the associations between different types of fermented dairy products, with various fat contents and dairy matrix structures, and blood lipid concentrations in a general population. Methods: In 11,377 women and men aged between 40-99 participating in the population-based Tromsø Study 2015-2016, multivariable linear regression was used to examine associations between total intake of fermented dairy products, intake of yoghurt (including regular-fat, low-fat, and semi-solid yoghurt), cheese (including regular-fat and low-fat), and liquid fermented dairy, and serum concentrations of total cholesterol, LDL-C, high-density lipoprotein cholesterol (HDL-C), and triglycerides. Dietary data was collected using a validated food frequency questionnaire. Analyses were adjusted for potential confounding factors, and cheese intake analyses were stratified by self-reported use of cholesterol-lowering drugs. Results: Cheese intake was positively associated with HDL-C (regression coefficient 0.02 mmol/l (95% CI 0.01, 0.03)), and inversely associated with LDL-C (regression coefficient -0.03 mmol/l (95% CI -0.04, -0.01)) and triglycerides (relative change -1.34 % (95% CI: -2.29 %, -0.37 %)) per 25 g/day among nonusers of cholesterol-lowering drugs, while no associations were found among users. Total intake of fermented dairy was inversely associated with triglycerides (relative change -1.11 % (95% CI: -1.96 %, -0.24%)) per 250 g/day, while no associations were found for yoghurt intake. Intake of low-fat cheese was more favorably associated with blood lipids compared to regular-fat cheese, and semi-solid yoghurt was inversely associated with LDL-C and triglycerides, while intake of liquid fermented dairy was not associated with any of the blood lipids. Conclusion: This study highlights the importance of investigating specific types of dairy products separately, based on fat content and dairy matrix, when examining effects on blood lipid concentrations, and stratifying statistical models by use of cholesterol-lowering drugs when relevant.